Meeting linguistic challenges in the science classroom: Pre-service ESL teachers' strategies - Saat, R.M.; Othman, J. (Taylor & Francis, 2010)
This study explores the perceptions and challenges of Malaysian pre-service teachers teaching science in a second language. A qualitative case study method was used with multiple sources of data to provide insights into the challenges that a group of pre-service teachers faced during their teaching practicum. The pre-service teachers had to overcome various challenges that arose due to factors such as lack of competency in the medium of instruction and the students' varying levels of language ability. In addressing the challenges faced, they employed various strategies, including code switching and mixing, teacher-student collaboration, rephrasing and re-emphasizing, the use of instructional aids, and the use of analogies. The evidence presented in this study suggests that attention should be given to addressing the English language policy in the science teacher education programme.